Community perception on government’s no-take zone management practices in Pulau Redang, Malaysia - Zailani, Nur Zaslin (2020)
No-take zones (NTZ) provide an effective implementation for biodiversity conservation and fisheries management. A key element of a NTZ’s success in marine and fisheries management is good governance which is important in decision-making. In addition, support from the local communities must also be taken into consideration in achieving NTZ success. Therefore, this study aims to determine the factors that influence the level of public perception of the governance of the No-take zone. The study area selected which is Pulau Redang, Terengganu includes the local community from Redang village (283 respondents). Pulau Redang of Terengganu has been identified as a marine park area including a no-take zone that offers an ecotourism site with its natural beauty and tourism activities. In addition, some of the local community on the island depends on the marine resources as fishermen. The problem statement highlighted is based on personal communication with the leaders of the local community. Lack of perceived benefits after the establishment of a no-take zone faced by the local community is the clear gap of the study. Thus, the general objective of the study is to analyse the perception of the local community on the governance of the no-take zone area in Pulau Redang. A quantitative method was used in this study. Questionnaire surveys were used to determine the level of community perception on the governance of a no-take zone area. Descriptive Statistics, Exploratory Factor Analysis and Multiple Regression Analysis were also performed to complete the data set. The descriptive findings showed positive perceptions of respondents on the governance of a no-take zone but they also have negative perceptions towards the governance of a no-take zone. The findings demonstrated the classification of the local community’s perception on the governance of a no-take zone into 16 means factors; ‘Equity and Fairness, Education of marine conservation essential for future generation, Efficiency of NTZ Administrative Resources, Awareness programme, Effort for conservation of Marine Park, Participation of Local Community, Information dissemination, Good cooperation between governance and community ,Level of enforcement activity , Disobey the rules and regulation, The changes of main job opportunities, Local Community aware of the marine park information, Opportunities for outsiders, A privilege for local fishermen, Governance Responsibility’ and ‘Existing solutions to the problems’. The actual findings of the study showed that two variables were significant in predicting the local community’s perception on the governance of a no-take zone; education level (ß = - 0.188, t = -4.799, p-value = .000) and married of marital status (ß = .148, t = 2.485, p-value = .014). This factor is important to ensure that the community always has a positive perception of effective government management. The findings of this study also provided some recommendations and suggestions which can be proposed to the local government especially the Department of Marine Parks and Tourism of Terengganu as the policy makers to formulate better conservation policies for enhanced conservation of marine resources as well as promoting a positive perception of the local community on the governance of a no-take zone.